ショウワキチ ニオケル チジキK シスウ - 小口, 高; オグチ, タカシ; OGUTI, Takasi (国立極地研究所, 1961)
P(論文) 昭和基地におけるK指数の撰択は,1959年2月より7月までの半年の資料に基いて行なわれ,その結果,K=9の最小Rangeを2500ガムマと決定した.このRangeにより1959年の1年間に於けるK瓦指数を求め,更にこれを,地球全体の平均的擾乱の指数と見做されるK_p指数と比較した.K_<Syowa>-K_pの関係は顕著な季節変化を示し,K値の小さい方では昼半球の極光帯の擾乱の方が夜半球のそれよりも大きく,逆にK値の大きい方では昼半球の擾乱は夜半球よりも小さいこと,即ち云いかえれば,小さい擾乱は昼半球の極光帯に起り易く,大きい擾乱は夜半球の極光帯に起り易いことが結論された. Range determination for K indices at Syowa Station (69°00'S, 35°39'E) is briefly discussed first, then the obtained values of K indices for about a year (from Feb. 8, 1959 to Jan. 9,1960) are tabulated. Some discussions are also given, especially on the seasonal variation of regression coefficient of K_<Syowa>. to K_p, which was known from correlation between X_<Syowa> and K_p for the period. departmental bulletin paper